2001
DOI: 10.1128/jb.183.5.1610-1620.2001
|View full text |Cite
|
Sign up to set email alerts
|

Effect of P II and Its Homolog GlnK on Reversible ADP-Ribosylation of Dinitrogenase Reductase by Heterologous Expression of the Rhodospirillum rubrum Dinitrogenase Reductase ADP-Ribosyl Transferase–Dinitrogenase Reductase-Activating Glycohydrolase Regulatory System in Klebsiella pneumoniae

Abstract: Reversible ADP-ribosylation of dinitrogenase reductase, catalyzed by the dinitrogenase reductase ADPribosyl transferase-dinitrogenase reductase-activating glycohydrolase (DRAT-DRAG) regulatory system, has been characterized in Rhodospirillum rubrum and other nitrogen-fixing bacteria. To investigate the mechanisms for the regulation of DRAT and DRAG activities, we studied the heterologous expression of R. rubrum draTG in Klebsiella pneumoniae glnB and glnK mutants. In K. pneumoniae wild type, the regulation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
32
0

Year Published

2001
2001
2003
2003

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 60 publications
(86 reference statements)
1
32
0
Order By: Relevance
“…After ammonium exhaustion, DraG becomes active, whereupon the modifying group is removed and nitrogenase activity is recovered. Recently, an involvement of PII-like proteins in the mechanism for the regulation of DraT and DraG has been demonstrated (32,40,64,65,66).…”
Section: Resultsmentioning
confidence: 99%
“…After ammonium exhaustion, DraG becomes active, whereupon the modifying group is removed and nitrogenase activity is recovered. Recently, an involvement of PII-like proteins in the mechanism for the regulation of DraT and DraG has been demonstrated (32,40,64,65,66).…”
Section: Resultsmentioning
confidence: 99%
“…In this regard, the very recent report of a reversible association of GlnK with the membrane that is AmtB and ammonium dependent is intriguing (8). The GlnK of Klebsiella pneumoniae has been shown to be involved in the posttranslational regulation of Rhodospirillum rubrum DraT and DraG when they are expressed in K. pneumoniae (55). While subsequent studies with R. rubrum have shown that these results cannot be strictly extrapolated to R. rubrum, it is clear that several of the R. rubrum P II proteins, namely, GlnB and GlnJ, are somehow involved in the posttranslational regulation of DraT and DraG in that organism (56).…”
Section: Discussionmentioning
confidence: 99%
“…In these experiments, as in other two-hybrid screens, caution should be used before any conclusions can be made concerning the validity of these new targets, and each will have to be verified in vivo or in vitro. On a positive note, however, an interaction with DRAT in this organism might be predicted from genetic evidence in the related organism Rhodospirillum rubrum (48).…”
Section: Glnk-ump Is Essential For Activation Of Gs In a Vinelandiimentioning
confidence: 99%